2012
DOI: 10.1002/ijc.27970
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell adhesion molecule is an independent prognostic marker in clear cell renal carcinoma

Abstract: Epithelial cell adhesion molecule (EPCAM) has recently attained a renewed interest as a candidate protein in diagnosis, prognostication and therapy of various tumor entities. The molecular epidemiology and prognostic relevance of EPCAM in renal cell carcinoma (RCC) and amongst the histological subtypes of RCC are unclear. We analyzed the prevalence and prognostic significance of EPCAM in a tumor tissue microarray composed of 1,088 independent RCCs samples by immunohistochemistry (IHC). We found significant var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
(78 reference statements)
4
11
2
Order By: Relevance
“…Our group could show that EpCAM can act both as tumour suppressor and tumour promotor28 29 in breast cancer cell lines and the dual role of EpCAM was confirmed by a recent study in breast cancer patients 30. Only recently, Eichelberg et al 31 reported a positive EpCAM status to be significantly associated with a prolonged overall survival in renal cell carcinoma. Moreover, the prognostic value of cytoplasmic accumulation of EpCAM was demonstrated in patients with node positive breast cancer 17.…”
Section: Discussionsupporting
confidence: 62%
“…Our group could show that EpCAM can act both as tumour suppressor and tumour promotor28 29 in breast cancer cell lines and the dual role of EpCAM was confirmed by a recent study in breast cancer patients 30. Only recently, Eichelberg et al 31 reported a positive EpCAM status to be significantly associated with a prolonged overall survival in renal cell carcinoma. Moreover, the prognostic value of cytoplasmic accumulation of EpCAM was demonstrated in patients with node positive breast cancer 17.…”
Section: Discussionsupporting
confidence: 62%
“…Although strong expression was seen in only 10 % of 318 ccRCC, EpCAM positivity correlated with improved survival. These results were confirmed by (Eichelberg et al 2013) who also observed no or only weak EpCAM expression in the majority of the 767 arrayed ccRCC. Positive EpCAM IHC was significantly linked to prolonged overall survival especially in patients with localized ccRCC.…”
Section: Proteomic Approaches Tissue Microarrays (Tma) For Evaluatingsupporting
confidence: 88%
“…In breast cancer cell lines, silencing of epcam by rna interference assays has been found to reduce cell proliferation and invasion 8 . Altered epcam expression correlates with aggressive biologic behavior in stomach, breast, kidney, and thyroid carcinomas [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%